The Role of Baitul Maal Wa Tamwil in The Economic Empowerment of Poor Women in Cianjur District - Uus Ahmad Husaeni (ITB AAS INDONESIA Surakarta, 2021)
This study aims to analyze BMT's role in poor women's economic empowerment in the Cianjur Regency. This research is a qualitative descriptive study using economic and sociological approaches. This research's data sources are primary data obtained from BMT and interviews and secondary data from library research. Furthermore, the data collection method is carried out by observation, interviews, and documentation for further analysis by reducing data, presenting data, and drawing conclusions. The results showed that BMT played a role in empowering the economy of women. Their income increases so that they can meet their daily needs and become more independent. Besides, they became smarter in managing finances and began to be actively involved in household decision making. Empowerment of women can improve women's welfare and independence in various aspects of life, particularly the economy. Applying the function of empowering women in microfinance institutions such as BMT is the right solution to improve the economy of the community, especially women